Gabapentin for treatment of restless legs syndrome among hemodialysis patients; a pilot study - Seyed Majid Mousavi Movahed; Gholamreza Alizadeh Attar; Fatemeh Hayati; Shahla Ahmadi Halili; Leila Sabetnia; Seyed Seifollah Beladi Mousavi (Society of Diabetic Nephropathy Prevention, 2018)
Introduction: Unfortunately the restless leg syndrome (RLS) is a neglected issue among hemodialysis (HD) centers. Objectives: The aim of our study was to find the efficacy of gabapentin at a low dose of 100 mg three times a week among HD patients with RLS. Patients and Methods: Around 21 patients with fulfilled the criteria of RLS were randomized to receive either gabapentin (100 mg) or placebo after HD session for 4 weeks. After 2 weeks of washout period, the patients were switched from gabapentin to placebo or placebo to gabapentin for another 4 weeks. Severity of RLS symptoms before and after management with medication or placebo was evaluated with standardized questionnaire. Results: Twenty-one patients (10 females and 11 males with mean age of 58 years) were enrolled to the study. Before the study, all patients had questionnaire scores of 16 or greater and the mean score was 24.19± 7.96. After gabapentin administration (before or after crossover), the mean score significantly decreased from 24.19± 7.96 to 19.24± 9.87 (P=0.04). The mean score before and after placebo administration (before or after crossover) were 24.19± 7.96 and 18.89± 11.15 with no significant difference (P=0.09). Conclusion: According to the results of the study gabapentin at a dose of 100 mg at the end of HD is a safe effective therapy for RLS. It can significantly reduce the intensity of RLS among these patients.